Croatia on the Triplex confinium: Two approaches - Blažević, Zrinka (Array, 2000)
This paper will focus on two perceptions of Croatia at the end of the 17th century. The first one is Croatia outlined in the memorandum Responsio ad postulata comiti Marsilio (1658-1730), dated 25 September1699, and written by Pavao Ritter Vitezović (1652-1713), Croatian polyhistor and one of the Commissioners of the Imperial Commission for Demarcation. However, in his report to the Emperor Leopold I of 29 December 1699 (Relazione di tutta la Croazia, considerata per il geografico, politico, economico e militare), Luigi Ferdinando Marsigli saw Croatia in a different way. Applying methods of the comparative analysis of these two manuscripts, both the correspondence between them and characteristics of Marsigli's reception of the memorandum, will be examined. Eventually, the author will try to reconstruct what Croatia looked like in the eyes of a diplomat and mercantilist L. F. Marsigli and a Croatian patriot and polyhistor P. R. Vitezović.